2018
DOI: 10.1111/joor.12636
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of wear between occlusal splint materials and resin composite materials

Abstract: Tooth wear in bruxing patients often results in a need for treatment with composite restorations. In some cases, bruxing patients receive an occlusal splint as a protective means as well. However, the wear between these opposing materials has not been investigated yet. The aim of this in vitro study was to assess the wear of different splint materials against resin composite materials. A two-body wear test was conducted using the ACTA wear machine. The materials selected for this study were three composites us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 21 publications
1
43
0
6
Order By: Relevance
“…Although minimal, the established changes have confirmed the fact that the CR position is not a fixed, static position, but that the CR is a range of possible positions dependent on the symmetrical mandibular muscle activity with a minimum level of muscle tone ( 27 ). In the interpretation of the results of larger condylar displacement in the CR in the experimental group, a change in the occlusal surface of the splint, irrespective of its fabrication material, should also be considered due to wear caused by parafunctional movements ( 33 ). A study comparing the effect of occlusal splints on the condyle position in subjects with TMD and asymptomatic control group showed that splints influenced the condyle position to a greater extent in the experimental group than in the control group after 10 weeks ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although minimal, the established changes have confirmed the fact that the CR position is not a fixed, static position, but that the CR is a range of possible positions dependent on the symmetrical mandibular muscle activity with a minimum level of muscle tone ( 27 ). In the interpretation of the results of larger condylar displacement in the CR in the experimental group, a change in the occlusal surface of the splint, irrespective of its fabrication material, should also be considered due to wear caused by parafunctional movements ( 33 ). A study comparing the effect of occlusal splints on the condyle position in subjects with TMD and asymptomatic control group showed that splints influenced the condyle position to a greater extent in the experimental group than in the control group after 10 weeks ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tiainen [20] studied tribological behaviour of PMMA in contact with different materials (4/10 MPa loads; pin-onplate reciprocating tests) and reported wear factors of PMMA as: 33/2510 -6 mm 3 /Nm and 0.086/0.04710 -6 mm 3 /Nm for CoCrMo and DLC-coated pins, respectively. Recent studies of PMMA wear reported wide ranges of wear rates depending on the PMMA preparation procedure [5,14]. Wear factors of the order of 710 -6 mm 3 /Nm can be found in the literature for dry sliding of a steel pin on PMMA, but without details on the steel type or test conditions [5,14].…”
Section: A R T I C L E I N P R E S Smentioning
confidence: 99%
“…Recent studies of PMMA wear reported wide ranges of wear rates depending on the PMMA preparation procedure [5,14]. Wear factors of the order of 710 -6 mm 3 /Nm can be found in the literature for dry sliding of a steel pin on PMMA, but without details on the steel type or test conditions [5,14]. Wear factors obtained in our study were in the range of 25-9010 -6 mm 3 /Nm for dry tests and 90-13010 -6 mm 3 /Nm for wet…”
Section: A R T I C L E I N P R E S Smentioning
confidence: 99%
See 2 more Smart Citations